Establishment of Foreign Political Relations of the Bukhara Khanty during the Ashtarkhanis and Mangit Dynasties (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
Historical studies testify that the development of Uzbek statehood was not smooth and that there were periods of triumph and crisis in its development. It is known to the world that the kingdom founded by the master Amir Temur was the largest and most powerful country. He left to his successors not only a powerful state but also the famous constitutions, which set out the rules for building a kingdom and governing the state. In particular, it states that "... let each of my children and descendants act according to it. ... They will use these rules as a guide in managing the affairs of their kingdom so that the state and the kingdom will be saved from the damage and decline that will reach them from me" [1:9]. However, his programs and wills were not fully followed. The political processes of the next period are clear proof of this.